Stereotactic aspiration and thrombolysis of spontaneous intracerebellar hemorrhage - Liu, Li; Shen, Hong; Zhang, Fan; Wang, Jing-He; Sun, Tao; Lin, Zhi-Guo (Chinese medical journal, 2011)
Background Spontaneous intracerebellar hemorrhage （SCH） accounts for 10% of intracerebral hemorrhages. Up to now stereotactic aspiration and thrombolysis of SCH was less reported. The aim of this study was to assess the effect and feasibility of the method, and to refine the clinical protocol. Methods Eighteen patients with SCH were treated by stereotactic aspiration and thrombolysis and reviewed in this report. The 3-ram axial stereotactic computed tomoaraDhv slices throughout the hematoma were obtained.